Pengaruh Inflasi Dan Nilai Tukar Terhadap Harga Saham (Studi Kasus Bank Mandiri (Persero) Tbk Yang Terdaftar Di Bursa Efek Indonesia Periode 2015-2018) - Karina Turi Lestari; Nanu Hasanuh (COSTING : Journal of Economic, Business and Accounting, 2021)
This study examines The Influence of Inflation and Exchange Rate on Stock Price Study Case of Mandiri Bank Listed in Indonesia Stock Exchange Period 2015-2018. Faculty of Economics University of Singaperbangsa Karawang. The independent variables are inflation and exchange rate, and the dependent variable is stock price. The researcher acquired sample within this study was by conducting purposive sampling method. Moreover, there were as many as 48 data of samples which were obtained within 4 years at Bank Mandiri for the period 2015-2018. The result imparts that the inflation does not influence Stock Price, and Exchange Rate has a significant negative effect on Stock Price. Inflation and Exchange Rate simultaneously have a significant effect on stock prices. Key Words : Stock Price, Inflation and Exchange Rate